An assessment of technology transfer in Malaysian manufacturers and the impact on performance and innovativeness - Jabar, Juhaini; Soosay, Claudine (2010)
Technology transfer through strategic technology alliances (STAs) is found to be a common initiative used by Malaysian manufacturing organizations to reap more effective outcomes. This study explores the influence of organizations’ available resources, absorptive capacity and opportunistic behavior on technology transfer; as well as the resultant impact on firm performance and innovativeness. This study is based on a larger research of Strategic Technology Alliances in Malaysian manufacturing organizations. The findings indicate that technology transfer is highly dependent on firms’ absorptive capacity, and can be capitalized for improved performance and innovativeness in firms. The study provides platforms and opportunities for more effective managerial decision making as well as strategic development and allocation of resources in the manufacturing industry. Additionally, this study also informs government’s business support service strategy in the economic and commercial viability of Malaysian manufacturing activities and products.